Music therapy influence in the reduction of moderately high blood pressure figures - Frank Miguel Hernández Velázquez; Belén de la Caridad Santiesteban Rodríguez; Raúl Javier Pizarro Hechevarría (Medisur)
Background: arterial hypertension is a disease with a high prevalence worldwide. Among the alternatives for its treatment, music therapy is effective together with pharmacological treatment. Objective: to describe the music therapy influence in the reduction of moderately high blood pressure figures. Methods: an observational, analytical, case-control study was carried out with patients (n=100) who attended the Rolando Ricardo Estrada Polyclinic’s Emergency Room, in the Báguanos municipality (Holguín), from 2021 to 2022, selected through purposive non- probabilistic sampling. Two groups of 50 patients each were created. The case group was exposed to music therapy, but not the control group. Results: in both groups, patients aged between 40 and 59 years (41%), female (55%) and with a previous diagnosis of arterial hypertension (58%) predominated. At the time of going to the polyclinic, systolic pressure between 140 and 159 mmHg (62%) predominated in both groups. After one hour had elapsed, in most of the patients in the case group the figures dropped to 120 and 139 mmHg (32%). In the control group, a slight decrease was observed, but a higher percentage of patients with 140 to 159 mmHg (25%) remained. Conclusion: patients exposed to music therapy showed a more marked decrease in moderately elevated blood pressure figures, compared to those not exposed.